If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -8) + 3(x + 2) = -4x + 8 Reorder the terms: 2(-8 + x) + 3(x + 2) = -4x + 8 (-8 * 2 + x * 2) + 3(x + 2) = -4x + 8 (-16 + 2x) + 3(x + 2) = -4x + 8 Reorder the terms: -16 + 2x + 3(2 + x) = -4x + 8 -16 + 2x + (2 * 3 + x * 3) = -4x + 8 -16 + 2x + (6 + 3x) = -4x + 8 Reorder the terms: -16 + 6 + 2x + 3x = -4x + 8 Combine like terms: -16 + 6 = -10 -10 + 2x + 3x = -4x + 8 Combine like terms: 2x + 3x = 5x -10 + 5x = -4x + 8 Reorder the terms: -10 + 5x = 8 + -4x Solving -10 + 5x = 8 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -10 + 5x + 4x = 8 + -4x + 4x Combine like terms: 5x + 4x = 9x -10 + 9x = 8 + -4x + 4x Combine like terms: -4x + 4x = 0 -10 + 9x = 8 + 0 -10 + 9x = 8 Add '10' to each side of the equation. -10 + 10 + 9x = 8 + 10 Combine like terms: -10 + 10 = 0 0 + 9x = 8 + 10 9x = 8 + 10 Combine like terms: 8 + 10 = 18 9x = 18 Divide each side by '9'. x = 2 Simplifying x = 2
| N-15=29 | | 4n+12= | | -2(-4)-6(-4)+-4= | | f+15=+16 | | (-4)-(-4)(2)+1= | | c/4=-20 | | -3(4p+3)-2(1-11p)=3(4+3P) | | 3x-6=10x-18 | | 88m-(44m-45)= | | 0.35x+0.25y=5.70 | | 6(-4)-3(-4)+13= | | -6(3b+3)+(19b-1)=0 | | 9(-4)-3(-4)= | | (15b-6)-7(2b+2)=-2 | | -13v+8-9v+12v= | | 19x-5(x-9x)+6x= | | 3y^2-16y=35 | | 8x+14x= | | 7d+10(1-6d)-4e= | | 7-x=-28 | | 3(n+5)=26 | | 17c+6(c-5c)-9c= | | X-7=28 | | -2(x-3)=x+5-3x | | 2x^2+2y^2=162 | | 15+8x-9(7x-3x)= | | 5.7q-2.8-4.9q=-0.2q-3.4 | | 8*30=12*x | | -4z+z-3(8z+6)= | | 13x+13=5x+5+7x | | -4(a+1)-3a=-7(2a-3) | | 21o-16p+3p+11p-9o= |